1998
DOI: 10.1159/000009956
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal Ultrasonographic Evaluation of the Endometrium Related to the Histological Findings in Pre- and Perimenopausal Women

Abstract: Our data indicate that transvaginal ultrasonography is as effective as the D&C for depicting the endometrium in pre- and perimenopausal women with irregular bleedings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The authors concluded that determining the upper limit of the ET in premenopausal women is useful in the clinical practice of office gynecology. In fact, in some reports that evaluated the efficacy of TVS for endometrial diseases in premenopausal women, the cut‐off value of the ET was determined without considering the menstrual cycle . The incidence of endometrial hyperplasia has been reported to be high in women with polycystic ovary syndrome or anovulation and it also has been reported that obesity and hypertension show a positive correlation with the ET.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors concluded that determining the upper limit of the ET in premenopausal women is useful in the clinical practice of office gynecology. In fact, in some reports that evaluated the efficacy of TVS for endometrial diseases in premenopausal women, the cut‐off value of the ET was determined without considering the menstrual cycle . The incidence of endometrial hyperplasia has been reported to be high in women with polycystic ovary syndrome or anovulation and it also has been reported that obesity and hypertension show a positive correlation with the ET.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have been published concerning the efficacy of TVS for endometrial cancer or hyperplasia in premenopausal women . One study performed TVS and dilatation and curettage (D&C) in 111 premenopausal women with AGB and reported that the median ET was 10.5 mm for all the women, while the recommended cut‐off value was 8.0 mm, the sensitivity was 83.9%, and the specificity was 58.8% .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure has two main drawbacks: first, it is an invasive procedure and has to be done under suitable anaesthesia; second, it may miss lesions such as polyps or endometrial carcinoma in not less than 10% of cases. 3 Hysteroscopy is another method that allows direct visualisation of the uterine cavity that can be used as an office technique in the evaluation of endometrial disorders. But due to its invasive nature, cost, limited use and lack of user skill, it cannot be made available everywhere, especially in economically burdened areas like ours.…”
Section: Introductionmentioning
confidence: 99%
“…For the direct diagnosis of endometrial pathology, TVS can reach a higher sensitivity once endometrial thickness is taken into account 9 . Transvaginal ultrasonography is as effective as the D&C (Dilatation and Curettage) for depicting the endometrium in pre, peri and post menopausal women with irregular bleedings 10 . On the basis of above facts this study is designed to establish the role of TVS as a sensitive tool used for evaluation of endometrial carcinoma.…”
Section: Introductionmentioning
confidence: 99%